Arteriovenous Oscillometric Plethysmography for Fistula Functional Testing - Veit Busch; Joachim Streis; Sandra Müller; Niklas Mueller; Felix S. Seibert; Thomas Felderhoff; Timm H. Westhoff (Karger Publishers, 2024)
Introduction: The aim of the presented prospective observational study was to evaluate the effect of fistula flow on peripheral wave morphology and pulse wave velocity by means of the oscillometric Vicorder®-device with the purpose of fistula surveillance. Methods: Digitized and normalized curves of 53 haemodialysis patients at the fistula and non-fistula arm were analysed. Slope parameters and the areas under the curve of characteristic sections of pulse waves as well as the power spectrum of the pulse waves and their first and second derivatives were computed. Furthermore, the amplitude of volumetric change (AMP) was assessed. Duplex sonography served as a reference method. Results: In the comprehensive set of novel pulse wave parameters significant inter-arm differences were demonstrated and a significant delay of the systolic maximum at the fistula arm in comparison to the non-fistula arm (204 ± 3.4 vs. 162 ± 5.3 ms, p < 0.001) was proven. Unexpectedly, pulse wave velocity apparently did not differ between both arms (7.85 vs. 8.05 m/s at the fistula/non-fistula side, p = 0.942). The inter-arm differences of the slope parameters were more pronounced in forearm than in upper arm fistulas. Finally, we showed that the inter-arm difference of AMP correlated with volume flow (r = 0.326 with p = 0.017). Conclusion: Pulse waves as assessed by oscillometric pulse wave analysis have distinct features at fistula and non-fistula arms. This is due to enhanced arteriovenous flow, i.e. in both the brachial artery and the fistula vein. The analysis of those alterations has the potential to assess fistula function.